Financial empowerment and entrepreneurial venture creation among NGOs' beneficiaries in Kwara State, Nigeria: An empirical investigation - Onaopemipo Adetoro Eletta; M. M. Adeyeye; Ademola Samuel Sajuyigbe (The Journal of Entrepreneurial Finance (JEF), 2021)
NGOs place much emphasis on the provision of diverse relevant training, counselling, mentoring, and financial empowerment in cash and equipment grants, loans and subsidies that made little or no impact on the lives of beneficiaries and the economy. Hence, this study examined the impact of financial empowerment and entrepreneurial venture creation among NGO beneficiaries in Kwara State, Nigeria. The study was posited on the empowerment theory. A survey was carried out employing the simple random sampling technique to select 358 respondents from a total of 5,354 sampling frame of NGOs' beneficiaries in Kwara State. Data analysis was performed using descriptive and inferential statistics. The results indicated that financial empowerment contributes significantly to entrepreneurial venture creation among the NGOs' beneficiaries. It was further revealed that cash loans and subsidies offered by NGOs have a positive impact on entrepreneurial venture creation, while grants have an inverse impact on entrepreneurial venture creation. The study, therefore, suggests among other things that the management of NGOs should scrutinize business plans properly before giving loans, grants, and subsidies to the beneficiaries so that only viable and innovative ideas will be funded. Also, they should offer training and enlightenment to beneficiaries to ensure the presence of unique and innovative activities and solutions pointing at entrepreneurial ventures creation.
Keywords: B26; J64; M13; 650; NGOs; Grants; Cash loans; Subsidies; Venture creation; Entrepreneurship; Innovation